Changing demographics of racialized people in Canada - Feng Hou; Christoph Schimmele; Max Stick (Economic and Social Reports, 2023)
In the past few decades, the number of racialized people in Canada has increased at a much faster rate than the population as a whole. This article uses data from the 2001 and 2021 censuses of population to examine population growth and changing demographics of racialized people. The study presents new data for 11 subgroups of the racialized population, their generational composition and changes in their share of people with a mixed racialized–White identity.